Energy distribution modulation by mechanical design for electrochemical jet processing techniques - Mitchell-Smith, Jonathon; Speidel, Alistair; Gaskell, Jennifer; Clare, Adam T. (Elsevier, 2017)
The increasing demand for optimised component surfaces with enhanced chemical and geometric complexity is a key driver in the manufacturing technology required for advanced surface production. Current methodologies cannot create complex surfaces in an efficient and scalable manner in robust engineering materials. Hence, there is a need for advanced manufacturing technologies which overcome this. Current technologies are limited by resolution, geometric flexibility and mode of energy delivery. By addressing the fundamental limitations of electrochemical jetting techniques through modulation of the current density distribution by mechanical design, significant improvements to the electrochemical jet process methods are presented. A simplified 2D stochastic model was developed with the ability to vary current density distribution to assess the effects of nozzle-tip shape changes. The simulation demonstrated that the resultant profile was found to be variable from that of a standard nozzle. These nozzle-tip modifications were then experimentally tested finding a high degree of variance was possible in the machined profile. Improvements such as an increase in side-wall steepness of 162% are achieved over a standard profile, flat bases to the cut profile and a reduction of profile to surface inter-section radius enable the process to be analogous to traditional milling profiles. Since electrode design can be rapidly modified EJP is shown to be a flexible process capable of varied and complex meso-scale profile creation. Innovations presented here in the modulation of resistance in-jet have enabled electrochemical jet processes to become a viable, top-down, single-step method for applying complex surfaces geometries unachievable by other means.